Belief Merging and Judgment Aggregation in Fuzzy Setting. (9th July 2012) - Beg, Ismat; Butt, Nabeel
Abstract : We explore how judgment aggregation and belief merging in the framework of fuzzy logic can help resolve the "Doctrinal Paradox." We also illustrate the use of fuzzy aggregation functions in social choice theory.